1958
DOI: 10.1107/s0365110x58001699
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of glutathione

Abstract: The tripeptide glutathione (y-~.-glutamyl-~-cysteinyl-glycine, Cx0H~;NaO~S) crystallizes in the orthorhombie system with space group P2~2~2~ and unit-cell dimensions a = 28-054-0-02, b----8.802+0"002, c = 5"630___0.002 A. The positions of the sulphur atoms in the unit cell were determined from the Harker sections of the three-dimensional Patterson ftmction.The structure was finally determined from a c-axis Fourier projection pattern based on terms with signs derived by the method of Cochran & Douglas, used in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

1973
1973
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(31 citation statements)
references
References 1 publication
2
29
0
Order By: Relevance
“…H(8) The C-S bond lengths and the C-S-C bond angle H(9) are in agreement with the corresponding values found H(10) H(ll) in glutathione (1.78A, Wright, 1958) .…”
supporting
confidence: 78%
“…H(8) The C-S bond lengths and the C-S-C bond angle H(9) are in agreement with the corresponding values found H(10) H(ll) in glutathione (1.78A, Wright, 1958) .…”
supporting
confidence: 78%
“…As a first step for these modeling studies, we surveyed the three-dimensional structures of GSH. In the crystalline state, GSH exhibits an extended Y-shape conformation (Wright, 1958), which is similar to the low-energy conformation Cedergren-Zeppezauer et al (1985 suggested that there are intermediate conformational states between the fully open and the fully closed conformations in ADH. This suggestion was based on a ''partially closed'' conformation observed in the Cys46-carboxymethylated EE-NADH structure.…”
Section: Orientation Of the Catalytic Domainmentioning
confidence: 98%
“…We felt that such a study was of particular value since, at the outset of our program, no crystallographic information on any linear peptide containing either Asp or Gla was available, and the only structural studies of Glu peptides involved the fully blocked dipeptide Z-(y-ethyl)-L-Glu-(Fethyl)-L-Glu-ethyl ester (Benedetti, DiBlasio, Pavone, Pedone, Germain & Goodman, 1979) and the y-glutamyl tripeptide glutathione (Wright, 1958). We have recently provided accounts of the crystal and molecular structures of the (Valente, Hiskey & Hodgson, 1979), and the free dipeptides tx-L-Asp-Gly.H20 (Eggleston, Valente & Hodgson, 1981a), ct-L-Glu-Gly (Eggleston, Valente & Hodgson, 1981b), and Gly-L-Asp.2H20 (Eggleston & Hodgson, 1981).…”
Section: Introductionmentioning
confidence: 99%